2021
DOI: 10.1016/j.cub.2021.05.019
|View full text |Cite
|
Sign up to set email alerts
|

KATANIN and CLASP function at different spatial scales to mediate microtubule response to mechanical stress in Arabidopsis cotyledons

Abstract: Highlights d Microtubules are persistent at cell contours exposed to high mechanical stress d Absence of both KATANIN and CLASP results in cells resembling soap bubbles d CLASP, unlike KATANIN, largely influences mechanoresponse only at the subcellular scale d Microtubule response to subcellular mechanical stress does not influence tissue shape

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 66 publications
3
48
0
Order By: Relevance
“…This difference in performance is not due to differences in topological features, since the normalized features showed similar distributions (Supplementary Figure 9). These results suggest a potential role of KATANIN in linking sub-and supracellular mechanical stress, known to affect leaf epidermal cells (Eng et al, 2021) and KATANINs role in positioning of the preprophase band, spindle, and phragmoplast (Komis et al, 2017). In addition, the cell geometry of the ktn mutant differs compared to the WT and might also influence the topology.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This difference in performance is not due to differences in topological features, since the normalized features showed similar distributions (Supplementary Figure 9). These results suggest a potential role of KATANIN in linking sub-and supracellular mechanical stress, known to affect leaf epidermal cells (Eng et al, 2021) and KATANINs role in positioning of the preprophase band, spindle, and phragmoplast (Komis et al, 2017). In addition, the cell geometry of the ktn mutant differs compared to the WT and might also influence the topology.…”
Section: Discussionmentioning
confidence: 83%
“…We grew Arabidopsis thaliana wild-type (WT; Wassilewskija ecotype) plants with the membrane reporter pUBQ10::acyl-YFP (previously described in (Willis et al, 2016)) and katanin1-2 mutant in Columbia-0 background with the membrane reporter Lti6b-GFP (Eng et al, 2021) in short day (8 h/16 h day/night), 20 °C/16 °C conditions for 3 weeks and then transferred to long day (16 h/8 h day/night), 20 °C/16 °C conditions till shoot apical meristem sampling. We cultured sampled shoot apical meristems (SAMs) in transparent imaging boxes containing apex culture media under long day, 22 °C conditions as previously described (Wang and Sampathkumar, 2020).…”
Section: Plant Materials and Growth Conditionmentioning
confidence: 99%
“…A limitation of this method is that it cannot provide three-dimensional shape information for cells because it captures only the cotyledon surface and is based on a two-dimensional approximation. To obtain three-dimensional structures of epidermal cells and their temporal changes (i.e., four-dimensional information), conventional confocal microscopy-based methods can be used (Wong et al, 2019;Haas et al, 2020;Higaki and Mizuno, 2020;Eng et al, 2021).…”
Section: Limitations and Strength Of The Proposed Methodsmentioning
confidence: 99%
“…The cotyledon pavement cells of most dicotyledonous plants have a simple rectangular shape just after germination, but drastically change into a jigsaw puzzle-like shape with waving lateral cell walls as the leaf expands (Higaki et al, 2016(Higaki et al, , 2017. The physiological significance of the jigsaw puzzle-like morphology has not been fully elucidated, although it has been suggested that it may have a role in strengthening the leaf surface (Glover, 2000), stomatal spacing (Glover, 2000;, organ-level morphogenesis (Kierzkowski et al, 2019;Eng et al, 2021), and reducing mechanical pressure on the cell wall from inside the cell (Sapala et al, 2018). Time-lapse observation is a fundamental and important technique for studying temporal changes of the epidermal cell morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation